2015
DOI: 10.1186/s12958-015-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of pig cumulus-oocyte complexes stimulated in vitro with follicle stimulating hormone or epidermal growth factor-like peptides

Abstract: BackgroundThe gonadotropin-induced resumption of oocyte meiosis in preovulatory follicles is preceded by expression of epidermal growth factor (EGF)-like peptides, amphiregulin (AREG) and epiregulin (EREG), in mural granulosa and cumulus cells. Both the gonadotropins and the EGF-like peptides possess the capacity to stimulate resumption of oocyte meiosis in vitro via activation of a broad signaling network in cumulus cells. To better understand the rapid genomic actions of gonadotropins (FSH) and EGF-like pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 97 publications
(113 reference statements)
2
28
0
3
Order By: Relevance
“…Widely used reference genes for expression analyses include GAPDH , ACTB , and HPRT (Blaha et al, 2015; Boosani, Dhar & Agrawal, 2015; Wang et al, 2016; Zhang et al, 2016b; Zhao et al, 2015). These genes are reported to have consistent expression levels under various conditions such as different organs and different developmental stages (Tang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Widely used reference genes for expression analyses include GAPDH , ACTB , and HPRT (Blaha et al, 2015; Boosani, Dhar & Agrawal, 2015; Wang et al, 2016; Zhang et al, 2016b; Zhao et al, 2015). These genes are reported to have consistent expression levels under various conditions such as different organs and different developmental stages (Tang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In pig cumulus cells, we found also that the most stable reference genes ( GAPDH/18S ) and expression dynamics of each reference gene during IVM were different from that of pig oocytes. In addition, although mRNA abundance studies in pig cumulus cells have been conducted frequently using HPRT/BACT/GAPDH as single internal control (Blaha, Nemcova, Kepkova, Vodicka, & Prochazka, ; Blaha, Nemcova, & Prochazka, and Yang et al., ), the systematic study on the selection of reference genes has not been performed yet until now. Thus, the combination of GAPDH/18S suitable as references for pig cumulus cells found in the present study could be used in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Blaha et alstudied the effect of FSH on ID1 gene expression pattern in porcine cumulus cells with microarray assays. They found that FSH administration led to increased expression of ID1 gene, and concluded that, since ID1 is responsible for cumulus cells differentiation and processes leading to successful IVM, may be potentially marker gene of oocyte maturational competence in vitro [2]. Hogg et al presented evidence that ID1 acts during embryogenesis and development promoting cell growth in sheep.…”
Section: Discussionmentioning
confidence: 99%